Influence of air velocity on thermal comfort and performance of students in naturally ventilated classrooms in tropical climate - Nor Azli, Mohamad Nor Azhari; Hariri, Azian; Chong, Zi Yao; Khasri, Muhammad Aidil; Muhamad Damanhuri, Amir Abdullah; Syazwan Mustafa, Mohd Syafiq; Kabrein, Hashim (2023)
Air velocity is among the most important factors influencing thermal comfort in naturally ventilated spaces in hot and humid tropical climates. It is important to have air velocity that suits comfort needs and enhances the student's learning performance in the classroom, especially in schools that rely only on natural ventilation assisted by ceiling fans. In this study, the thermal comfort and learning performance of students in a selected naturally ventilated classroom at a secondary school in Segamat, Johor, Malaysia, were experimentally evaluated under different air velocity conditions during the peak temperature period during the school session. Throughout the experiment, physical measurement and a subjective evaluation questionnaire were conducted for thermal comfort analysis and to gather the student's thermal environment evaluation in the classroom. Students' learning performance was assessed through simple reaction and digit span tests based on the WHO Neurobehavioral Core Test Battery (NCTB). All the assessment results were statistically analyzed, and the relationships among indoor air velocity, thermal comfort, and learning performance were obtained. The result showed optimal learning performance was significant when students felt "slightly cool"and air velocity was more than 0.95 m/s. Hotter environments and a lack of air movement were found to be causes of declining student performance. In conclusion, it is suggested that the comfort zone in a naturally ventilated classroom for school students should be set within the range of -1 (slightly cool) with an air velocity greater than 0.76 m/s.